2020
DOI: 10.3390/genes11080876
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Landscape of the Mitochondrial Genome in the United Arab Emirates Native Population

Abstract: In order to assess the genomic landscape of the United Arab Emirates (UAE) mitogenome, we sequenced and analyzed the complete genomes of 232 Emirate females mitochondrial DNA (mtDNA) within and compared those to Africa. We investigated the prevalence of haplogroups, genetic variation, heteroplasmy, and demography among the UAE native population with diverse ethnicity and relatively high degree of consanguinity. We identified 968 mtDNA variants and high-resolution 15 haplogroups. Our results show that the UAE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…Additionally, we found in the Emirates the African A and B haplogroups and the predominantly South Asian haplogroups L1 and R2, mirroring admixture patterns we detected from genome-wide analysis. Similarly, we found African mitochondrial (mtDNA) haplogroup L in the Emirate with a frequency of $15%, almost twice as high as previously reported from the Emirates (Aljasmi et al 2020). Although the South Asian haplogroups U2-U4 were $8% in our data set.…”
Section: Y Chromosome and Mitochondrial Haplogroup Analysissupporting
confidence: 86%
“…Additionally, we found in the Emirates the African A and B haplogroups and the predominantly South Asian haplogroups L1 and R2, mirroring admixture patterns we detected from genome-wide analysis. Similarly, we found African mitochondrial (mtDNA) haplogroup L in the Emirate with a frequency of $15%, almost twice as high as previously reported from the Emirates (Aljasmi et al 2020). Although the South Asian haplogroups U2-U4 were $8% in our data set.…”
Section: Y Chromosome and Mitochondrial Haplogroup Analysissupporting
confidence: 86%
“…Natural selection 3 , 8 , 17 is often considered an important component in the evolution of the MHC and the production of CEHs. However, evident by the information presented here and other reports 42 44 , it seems that the MHC genomic landscape of the contemporary UAE nationals must have also been shaped by both transcontinental migration between Africa, Asia, and Europe, which involved a diverse array of ethnic groupings 34 , 51 , and the nomadic lifestyles of some Arabian communities, notably the Bedouins.…”
Section: Discussionmentioning
confidence: 56%
“…Following that, a comprehensive, large-scale stratification study of the UAE population concluded that genetic admixture throughout the Arabian Peninsula's eastern shore and south-eastern tip happened gradually and without clear social stratification boundaries 43 . This, and another mitogenome study 44 , have shown that there was no apparent association between birthplace and ancestral background, indicating that the contemporary UAE population developed over generations prior to the establishment of the current political borders with a significant genetic influence from the Middle East, Central/South Asia, and Sub-Sahara 43 .…”
Section: Discussionmentioning
confidence: 73%
“…Since the earliest modern human emerged from Africa, multiple maternal lineage migratory events favoring African-Asian corridors have occurred, according to the research based on UAE mitogenomes [157]. Ancestral sharing with Africa, the Near East and East Asia was also revealed from the study [157].…”
Section: P R E P R I N Tmentioning
confidence: 94%
“…The report from Emirati population showed that the Arab population received sufficient gene flow from African ancestries. Furthermore, the study showed that the Arab population received sufficient gene flow from Africa ancestries and a demographic bottleneck was observed that occurs around the time of Western European contact [157].…”
Section: P R E P R I N Tmentioning
confidence: 97%